CT-Detected Growth of Coronary Artery Calcification in Asymptomatic Middle-Aged Subjects and Association With 15 Biomarkers - Diederichsen, Søren Zöga; Grønhøj, Mette Hjortdal; Mickley, Hans; Gerke, Oke; Steffensen, Flemming Hald; Lambrechtsen, Jess; Rønnow Sand, Niels Peter; Rasmussen, Lars Melholt; Olsen, Michael Hecht; Diederichsen, Axel (JACC. Cardiovascular imaging, 2017)
This study sought to determine the incidence and progression of coronary artery calcification (CAC) in asymptomatic middle-aged subjects and to evaluate the value of a broad panel of biomarkers in the prediction of CAC growth. CAC continues to be a major risk factor, but the value of biochemical markers in predicting CAC incidence and progression remains unresolved. At baseline, 1,227 men and women underwent traditional risk assessment and a computed tomography (CT) scan to determine the CAC score. Biomarkers of calcium-phosphate metabolism (calcium, phosphate, vitamin D3, parathyroid hormone, osteoprotegerin), lipid metabolism (triglyceride, high- and low-density lipoprotein, total cholesterol), inflammation (C-reactive protein, soluble urokinase-type plasminogen activator receptor), kidney function (creatinine, cystatin C, urate), and myocardial necrosis (cardiac troponin I) were analyzed. A second CT scan was scheduled after 5 years. General linear models were performed to examine the association between biomarkers and ΔCAC score, and additionally, sensitivity analyses were performed in terms of binary and ordinal logistic regressions. A total of 1,006 participants underwent a CT scan after 5 years. Among the 562 participants with a baseline CAC score of 0, 189 (34%) had incident CAC, whereas 214 (48%) of the 444 participants with baseline CAC score >0 had significant progression (>15% annual increase in CAC score). In the multivariate models (n = 1,006), age, sex, hypertension, diabetes, dyslipidemia, and smoking were associated with ΔCAC, whereas the strongest predictor was baseline CAC score. Low-density lipoprotein and total cholesterol levels were independently associated with CAC incidence (n = 562; incidence rate ratio [IRR]: 1.47; 95% confidence interval [CI]: 1.05 to 2.05; and IRR: 1.34; 95% CI: 1.01 to 1.77, respectively), whereas phosphate level was associated with CAC progression (n = 444; IRR: 3.60; 95% CI: 1.42 to 9.11). In this prospective study, a large part of participants had incident CAC or progression of prevalent CAC at 5 years of follow-up. Low-density lipoprotein and total cholesterol were associated with CAC incidence and phosphate with CAC progression, whereas 12 other biomarkers had little value. [Display omitted]